Implementasi Augmented Reality Furniture Dengan User-Defined Target Berbasis Android - Junaidi, Akmal; Prabowo, Rizky; Syarif, Admi; Fazri, Yudistira (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Furniture catalogs display items statically in 2-dimensional form only. Buyers often want to observe furniture in a real room. Home-View application in this study can display 3D furniture objects as they want. Home-View App has been developed with Augmented Reality technology. Application is developed using the Vuforia SDK library and User Defined Target (UDT) method in the Unity3D software. UDT is utilized to display 3D furniture on a target like magazine and book covers. Home-View application has two menus namely Marker Katalog and HomeView. Marker Katalog serves as a method to view 3D furniture in a small form in the furniture catalog. HomeView serves as a way to view 3D furniture in the desired room. This application has a positioning feature on the x and y axis and rotating feature on the z axis. The application can run by displaying 3D furniture to its actual size at the HomeView menu and successfully displaying 3D furniture as listed on the catalog at the Marker Katalog menu.